Length of stay and associated costs of obesity related hospital admissions in Ireland - O'Donovan Diarmuid; Vellinga Akke; De La Harpe Davida (BMC, 2008)
Abstract Background Obesity is the cause of other chronic diseases, psychological problems, obesity shortens the lifespan and puts strain on health systems. The risk associated with childhood obesity in particular, which will accelerate the development of adult morbidity and mortality, has been identified as an emerging public health problem. Methods To estimate the length of stay and associated hospital costs for obesity related illnesses a cost of illness study was set up. All discharges from all acute hospitals in the Republic of Ireland from 1997 to 2004 with a principal or secondary diagnostic code for obesity for all children from 6 to 18 years of age and for adults were collected. A discharge frequency was calculated by dividing obesity related discharges by the total number of diagnoses (principal and secondary) for each year. The hospital costs related to obesity was calculated based on the total number of days care. Results The discharge frequency of obesity related conditions increased from 1.14 in 1997 to 1.49 in 2004 for adults and from 0.81 to 1.37 for children. The relative length of stay (number of days in care for obesity related conditions per 1000 days of hospital care given) increased from 1.47 in 1997 to 4.16 in 2004 for children and from 3.68 in 1997 to 6.74 in 2004 for adults. Based on the 2001 figures for cost per inpatient bed day, the annual hospital cost was calculated to be 4.4 Euromillion in 1997, increasing to 13.3 Euromillion in 2004. At a 20% variable hospital cost the cost ranges from 0.9 Euromillion in 1997 to 2.7 Euromillion in 2004; a 200% increase. Conclusion The annual increase in the proportion of hospital discharges related to obesity is alarming. This increase is related to a significant increase in economic costs. This paper emphasises the need for action at an early stage of life. Health promotion and primary prevention of obesity should be high on the political agenda.